Physiological Basis of the Couvade Syndrome and Peripartum Onset of Bipolar Disorder in a Man: A Case Report and a Brief Review of the Literature - Giourou, Evangelia; Skokou, Maria; Andrew, Stuart Peter; Gourzis, Philippos (Frontiers in Psychiatry, 2018)
Rapid hormonal changes during pregnancy as well as psycho-social stressors accompanying parenthood have often been associated with peripartum mood episodes in women with bipolar disorder or with not yet clinically expressed bipolar diathesis. Yet, little is known about the correlation of peripartum onset of bipolar disorder in men. We present the case of a man with bipolar disorder with peripartum onset and subsequent episodes following the peripartum initiation of the disease, as well as the association of the couvade syndrome, as a pathological response to a man due to hormonal shifts observed in males cohabiting with a pregnant female. The patient had his first depressive episode during the peripartum period of his spouse, followed by two mixed episodes with psychotic features that leaded to his compulsory psychiatric evaluation and subsequent hospitalization and the diagnosis of Bipolar Disorder I. There is a well-known correlation between the peripartum period and mood disturbances to the point of inducing full blown episodes, suggesting of a bipolar disorder initiation or mood episodes relapsing in female patients already diagnosed with bipolar disorder. Due to the patient's psychological disturbances and the phenomenology of his symptoms, mainly concerning the psychotic features accompanying his episodes, we discuss the possible underlying biological correlates as a triggering mechanism, that might overlap the manifestation of the Couvade Syndrome as well as the initiation or relapse of Bipolar Disorder in males. It seems that males are not less influenced by hormonal and psycho-social factors posed upon them during the peripartum period of their cohabiting female spouse.